Electronic structure, density of electronic states, and the chemical bonding properties of 2,4-dihydroxyl hydrazone crystals (C13H 11N3O4) - Ali Hussain, Reshak, Prof. Dr. (Springer Science+Business Media New York., 2014)
Link to publisher's homepage at http://link.springer.com/